2016
DOI: 10.1017/jfm.2015.758
|View full text |Cite
|
Sign up to set email alerts
|

Tank-treading of microcapsules in shear flow

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…Interestingly, Yazdani & Bagchi (2013) have studied the contribution of shear surface viscosity to the dynamics of capsules. They showed notably that the period of tank-treading varies with membrane viscosity, a result recently confirmed by experimental investigations on HSA microcapsules (de Loubens et al 2015b). However, the computation of bending stiffness was found to be necessary for capsules, in order to suppress wrinkling.…”
Section: Introductionmentioning
confidence: 79%
“…Interestingly, Yazdani & Bagchi (2013) have studied the contribution of shear surface viscosity to the dynamics of capsules. They showed notably that the period of tank-treading varies with membrane viscosity, a result recently confirmed by experimental investigations on HSA microcapsules (de Loubens et al 2015b). However, the computation of bending stiffness was found to be necessary for capsules, in order to suppress wrinkling.…”
Section: Introductionmentioning
confidence: 79%
“…The determination of the surface viscous modulus of the membrane is out of the scope of this paper. This parameter is difficult to determine by experiments on microcapsules as we need to track the movement of the membrane in shear flow and deduce the viscous modulus from inverse numerical simulations 22,41 .…”
Section: Elongation Flow Chambermentioning
confidence: 99%
“…More recently, these methods have been extended to micrometric capsules [34][35][36][37][38] . By combination with advanced numerical simulations 21,22,39 , the nonlinear elastic constitutive laws in regime of large deformation 40 and the viscosity of the membrane 41 have been determined for microcapsules made from a biopolymer (HSA) that was physically cross-linked to form a thin membrane in hydrogel. It was shown that this kind of microcapsules can sustained up to 180% of stretching without plastic deformations or break-up.…”
Section: Introductionmentioning
confidence: 99%
“…It is then straightforward to construct matrix form of the relations between on the one hand limit values of tension ({γ}) and limit values of tension forces ({f γ }), and on the other hand, between limit values of velocities ({v}) and limit values of surface divergence ({∇ s • v}). To finish the approximation of D γ , the linear relation between limit values of forces ({f }) and limit values of velocities ({v}) expressed by (16) without viscosity contrast (λ = 1) is discretized over the linear mesh as in [7] by using Gauss-Hammer quadrature for non-singular elements and Gauss-Legendre quadrature with polar coordinates for singular elements. Thus, with the matrices F γ , D, G defined by the preconditioner D γ is defined as…”
Section: Surface Incompressibility Constraint Solvermentioning
confidence: 99%